The Contravention and Community Alteration Relationship - Gunawan Indra Permana; Akhmad Saiful; Iskandarsyah Siregar; Zulkarnain Zulkarnain (Budapest International Research and Critics University, 2022)
Contravention and community alteration are a couple that influences each other. Contravention inevitably drives community alteration. Community alterations also inevitably lead to the contravention. These conditions can manifest in large or small sizes. Every society that exists on this earth in their life will certainly experience what is called changes. These changes will be known if we compare by examining association at a particular time which we then reach with the state of society in the past. Changes that occur in the community are a continuous process. This situation means that every organisation will, in fact, experience changes. This study aims to collect argumentative views on the relationship between contravention and community alteration. The conclusions of this study have a significant impact in providing illustrations and projections of what social situations occur before and after contraventions or community, alterations arise. This research is a discourse relation analysis research. This type of research analyses the relationship between two or more variables and then describes each contextual factor. This study concludes that the argumentative view of implying and exposing the relationship of contravention to community alteration is vital and sensitive.